The Effect of Music towards the Reducing of Stress Levels in Young People - Djohan -; Fortunata Tyasrinestu (Institut Seni Indonesia Yogyakarta, 2018)
These quasi-experiment research aims to identify any effect of music activities as media to reduce stress hassle on the subject which attend in the choir group. The musical repertoire which was used was the pop genre which technically did not have much complexities and the lyric straightforward to understand. Hassle stress is a stressor that involves minor everyday events such as traffic jam, activities of queuing, forgetfulness in putting the things, or turmoil. Manipulation or treatment treated to the subject as a member of the choir is totally N=10. The treatment was the singing rehearsal. The tools for collecting data were a questioner of self-report which contained questions and QRMA (Quantum Resonance Magnetic Analyzer) measurement which also focused on group discussion. The result shows that there is an effect of musical activities as media for reducing the stress hassle and promoting the previous research results. Some analysis shows that there should be an experiment with a different musical repertoire because a difference genre needs a different skill and there should be a necessity to measure a physical condition more accurately by QRMA to all participants.